Red Hat Fedora Linux 2 All-in-One Desk Reference for Dummies - Barkakati, Naba (Wiley Publishing, 2011)
This essential reference organizes material into a set of nine stand-alone, task-oriented minibooks that enable readers to understand all aspects of the Fedora OS, the latest release of the most popular Linux distribution Each minibook covers a different aspect of Fedora, such as getting users started with Fedora, the various workstations and applications, OpenOffice.org, networking, system administration, security, running Internet servers on a Fedora system, and programming More experienced readers can use this desktop reference to look up how to perform specific tasks, such as hooking up to the Internet, using a cable modem, or reading e-mail Includes the full Fedora Core distribution with source code on DVD and all of the CD content that comes with Fedora, saving readers hours of download time